Carbon-based π-complex materials for removing CS2 from gasification fuels of organic solid waste, their preparation methods and applications
Patent Information
- Application Number
- CN202510382908.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-03-28
AI Technical Summary
[0005]上述现有技术中使用的单一成分海藻酸钠气凝胶还存在以下缺点:(1)机械强度较低:容易在使用过程中发生坍塌或变形;(2)空隙率和吸附性能有限:虽具有较高的孔隙率,但内部结构不均匀,导致吸附性能不稳定
[0026] (1) In this invention, a carbon-supported hydrogel consisting of sodium hyaluronate, mannitol, and dried sodium alginate is selected as the carrier for the carbon-based π-complex material. During the drying process, the polysaccharide chains of sodium alginate undergo pyrolysis, removing oxygen-containing functional groups, and the remaining carbon atoms rearrange themselves. 2 Hybridization forms an aromatic carbon skeleton, which can combine with more metal ions, generating more adsorption sites for adsorbing gaseous organic and inorganic sulfur pollutants, thus offering greater advantages in terms of cost-effectiveness and removal efficiency.
Smart Images

Figure CN120205092B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of organic solid waste gasification fuel technology, specifically to a carbon-based π-complex material for removing CS2 from organic solid waste gasification fuel, its preparation method, and its application. Background Technology
[0002] Organic solid waste is characterized by its dispersed sources, large output, and complex composition, possessing both resource and pollution attributes. It mainly includes agricultural organic waste, industrial organic waste, and municipal solid waste. Organic sulfur is primarily found in waste plastics, waste rubber, textiles, and kitchen waste. During the gasification of organic solid waste into fuel gas, sulfur will enter the fuel gas as gaseous sulfur pollutants. The presence of gaseous sulfur accelerates the corrosion of metal pipes and equipment, shortening their service life. Furthermore, the CS2 and dioxin pollutants generated during combustion can easily cause catalyst poisoning during catalytic processing and will be released into the atmosphere during combustion.
[0003] Existing technologies utilize sodium alginate aerosols to adsorb CS2 from the gasification fuel of organic solid waste. Research reports on sodium alginate aerosols mainly include:
[0004] Application No. 202111409037.6 discloses a method for preparing a highly catalytically active copper alginate aerosol catalyst. The method uses sodium alginate, a biomass polymer, as a raw material. Iminodiacetic acid reacts with sodium alginate via an amidation reaction, converting the monocarboxyl groups in the sodium alginate structural units into dicarboxyl groups. This is then crosslinked with divalent copper ions, and after freeze-drying, a highly catalytically active copper alginate aerosol catalyst is obtained. Application No. 202411982606.X discloses a method for preparing floating copper-supported sodium alginate hydrogel spheres. Solution A consists of sodium alginate, citrate, an acidic pH adjuster, hydrogen peroxide, and water; solution B consists of copper sulfate pentahydrate, citrate, a pH adjuster, and water. Solution A is added dropwise to solution B to obtain hydrogel spheres. Application No. 202310832697.8 discloses a three-dimensional silver-based composite aerogel, its preparation method and application. Poly(acrylamide-co-acrylic acid) / sodium alginate carbon aerogel is prepared by sintering, and then a three-dimensional silver-based composite aerogel with high specific surface area and high catalytic activity is prepared by in-situ deposition using silver nitrate as a precursor solution.
[0005] The single-component sodium alginate aerogel used in the above-mentioned prior art also has the following disadvantages: (1) Low mechanical strength: It is easy to collapse or deform during use; (2) Limited porosity and adsorption performance: Although it has a high porosity, the internal structure is not uniform, resulting in unstable adsorption performance. Its adsorption capacity and adsorption rate are low, making it difficult to meet the requirements of high-efficiency adsorption; (3) Poor thermal stability: It is easy to cause structural damage under high temperature conditions, which limits its application in high-temperature environments; (4) Poor resistance to space velocity: Under high space velocity conditions, the pore structure in the adsorbent material is easy to collapse, making it impossible to achieve adsorption under high space velocity; (5) Poor reusability: It cannot be completely desorbed during repeated use, resulting in a reduction of adsorption sites, thereby affecting its reusability efficiency.
[0006] This shows that the existing technology needs further improvement. Summary of the Invention
[0007] One of the objectives of this invention is to provide a method for preparing a carbon-based π-complex material for removing CS2 from gasification fuel of organic solid waste. The carbon-based π-complex material prepared by this invention can remove gaseous pollutant CS2 from gasification fuel of organic solid waste under room temperature and high space velocity conditions, and the removal efficiency is excellent.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] A method for preparing a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste includes the following steps:
[0010] a. Mix sodium hyaluronate, mannitol and dried sodium alginate in a certain ratio to prepare mixed solution one;
[0011] b. Prepare solution A: Mix dimethylformamide and methyl acrylate;
[0012] Solution B is prepared by mixing polystyrene microspheres with a surfactant and then adding phenylboronic acid, which causes the polystyrene microspheres to form chemical bonds with the phenylboronic acid.
[0013] Solution A and solution B are mixed to form mixed solution two;
[0014] Add the second mixed solution to the first mixed solution, then add sodium tripolyphosphate as a crosslinking agent, and stir while controlling the reaction temperature at 40-60°C to obtain the third mixed solution;
[0015] c. Using the microwave impregnation method, add three drops of the mixed solution to a solution containing Sr. 2+ Gd 3+ In a salt solution, a hydrogel doped with metal ions was obtained;
[0016] d. The hydrogel doped with metal ions is dried, frozen, and then carbonized by high-temperature calcination under a nitrogen atmosphere to obtain carbon-based π-complex materials.
[0017] In the above-mentioned method for preparing a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste, in step a, the mass ratio of sodium alginate, sodium hyaluronate, and mannitol is 1-2:1-4:1-4, the solvent of mixed solution one is water, and the total mass percentage of sodium alginate, sodium hyaluronate, and mannitol in mixed solution one is 6-8%; the drying temperature of sodium alginate is 600℃.
[0018] In the above-mentioned method for preparing a carbon-based π-complex material for removing CS2 from the gasification fuel of organic solid waste, in step b, the total amount of dimethylformamide and methyl acrylate added is 15-35% of the total mass of sodium hyaluronate, mannitol, and sodium alginate; the amount of polystyrene microspheres and surfactant added is 3-5% of the total mass of sodium hyaluronate, mannitol, and sodium alginate; the surfactant is hexadecyltrimethylammonium chloride; the amount of crosslinking agent added is 60% of the total mass of sodium hyaluronate, mannitol, and sodium alginate; and the amount of phenylboronic acid added is 0.3 times the amount of polystyrene microspheres added.
[0019] In the above-mentioned method for preparing a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste, in step c, Sr 2+ Gd 3+ The mass ratio of the two metals in the salt solution is 1:1, Sr 2+ Gd 3+ The salt solutions are Sr(NO3)2 and Gd(NO3)3·6H2O.
[0020] In the above-mentioned method for preparing a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste, in step c, the microwave impregnation time is 20-40 min, the impregnation temperature is 40-50℃, and the microwave frequency is 200 GHz.
[0021] In the above-mentioned method for preparing a carbon-based π-complex material for removing CS2 from the gasification fuel of organic solid waste, in step d, the carbonization temperature is 300-900℃ and the carbonization time is 1-3h. After carbonization, the metal ions in the hydrogel doped with metal ions are oxidized to their corresponding oxides to adsorb CS2 in the gasification fuel of organic solid waste.
[0022] In the above-mentioned method for preparing a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste, in step a, sodium alginate is used as a carrier, mannitol is used as an excipient for the sodium alginate carrier, and sodium hyaluronate is used as a water-retaining agent to facilitate the removal of CS2.
[0023] Another objective of this invention is to provide a carbon-based π-complex material prepared by the above-mentioned method for removing CS2 from gasified fuel gas of organic solid waste, wherein the carbon-based π-complex material has a layered structure.
[0024] Another object of the present invention is to provide the application of the aforementioned carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste, wherein the carbon-based π-complex material is used in a fixed-bed reactor under simulated gas conditions with a space velocity of 60,000 h⁻¹. -1 CS2 is removed from the gasification fuel of organic solid waste at a temperature of 25℃; the simulated gas contains 40% CH4, 20% CO, 35% H2 and 5% CS2 by mass percentage, wherein the concentration of CS2 is 200ppm.
[0025] Compared with the prior art, the present invention brings the following beneficial technical effects:
[0026] (1) In this invention, a carbon-supported hydrogel consisting of sodium hyaluronate, mannitol, and dried sodium alginate is selected as the carrier for the carbon-based π-complex material. During the drying process, the polysaccharide chains of sodium alginate undergo pyrolysis, removing oxygen-containing functional groups, and the remaining carbon atoms rearrange themselves. 2 Hybridization forms an aromatic carbon skeleton, which can combine with more metal ions, generating more adsorption sites for adsorbing gaseous organic and inorganic sulfur pollutants, thus offering greater advantages in terms of cost-effectiveness and removal efficiency.
[0027] (2) This invention uses polystyrene microspheres as a template agent. Polystyrene generates a graphitized carbon structure at high temperature, which then undergoes π-π complexation with the aromatic region of the porous carbon structure of sodium alginate to generate a layered carbon-based π-complex adsorbent material. The layered adsorbent structure has high thermal and chemical stability, can be regenerated in high-temperature environments, has a high number of reuses, reduces long-term application costs, and is suitable for industrial-grade adsorption equipment.
[0028] (3) In this invention, dimethylformamide and methyl acrylate are used together to regulate solubility and control the film-forming properties of the hydrogel, which facilitates the subsequent loading of metal ions and the doping of phosphorus. At the same time, both are suitable for high-temperature polymerization systems, ensuring the structural integrity of the adsorbent material during high-temperature calcination, preventing pore collapse, and effectively improving the adsorbent yield.
[0029] (4) The present invention uses microwave impregnation method, adding three drops of the mixed solution to a concentration of Sr. 2+ Gd 3+In the salt solution, the microwave process runs through the chelation and cross-linking process between the hydrogel and metal ions; the microwave impregnation method is conducive to the pore formation of the cross-linking agent. By controlling the pore size of the carbon-based π complex material by different microwave frequencies, the proportion of different pore sizes in the carbon-based π complex material is increased, the internal support structure of the carbon-based π complex material is enhanced, and the different pore sizes inside the carbon-based π complex material are interconnected to form a network structure with strong heterogeneity and anisotropy, thereby improving the adsorption effect of the carbon-based π complex material.
[0030] (5) In this invention, polystyrene microspheres and hexadecyltrimethylammonium chloride are added to a mixed solution of sodium alginate, sodium hyaluronate and mannitol. After high-temperature calcination and carbonization, the polystyrene microspheres develop hydroxyl groups (-OH), which chemically bond with the boric acid groups (B(OH)2) in phenylboronic acid to form borate bonds (BO), thereby forming a cross-linked structure between the polystyrene chains. This makes the adsorbent material structure more robust, forming a carbon-based π-complex material with a large specific surface area and porous structure. Hexadecyltrimethylammonium chloride acts as a surfactant to reduce the surface tension of the polystyrene microspheres during the preparation of the carbon-based π-complex material, allowing sodium alginate and metal ions to chelate with the polystyrene microspheres better. The combination of polystyrene microspheres and hexadecyltrimethylammonium chloride results in a carbon-based π-complex material with a more complete internal structure.
[0031] (6) In the preparation of the mixed solution, sodium tripolyphosphate was added as a crosslinking agent, which simultaneously achieved phosphorus doping and increased the number of adsorption active sites. This invention uses Sr and Gd metal oxides loaded onto the surface or pores of the carbon-based π-complex material carrier, which can significantly increase the number of active sites in the carbon-based π-complex material. By controlling the interaction force between the carrier and the metal oxide, the electron cloud density of the oxide can be effectively reduced, and local defects and oxygen vacancies can be generated, thereby significantly improving the desulfurization performance of the carbon-based π-complex material.
[0032] (7) The adsorption of organic sulfur CS2 by the carbon-based π-complex material adsorbent of the present invention is a π-complex adsorption process. The central carbon atom of CS2 is sp hybridized to form two delocalized π bonds. The adsorbent is doped with metal Sr 2+ It possesses a 5s empty orbital. Electrons transfer from the π orbital of the organic sulfide CS2 to the empty s orbital of the adsorbent metal atom, which is called π-complex adsorption. The π-electron system of the π-complex adsorbent can form directional interactions with gaseous pollutants containing π bonds, enabling highly efficient adsorption. Attached Figure Description
[0033] The present invention will be further described below with reference to the accompanying drawings:
[0034] Figure 1 This is an electron microscope image of the carbon-based π-complex material prepared in Example 1 of the present invention;
[0035] Figure 2 The amount and efficiency of CS2 removal by carbon-based π-complex materials prepared under different embodiment conditions;
[0036] Figure 3 The amount of CS2 removed and the removal efficiency after three adsorption / regeneration cycles in Example 1 are shown (the three regeneration cycles are represented as R1, R2 and R3, respectively). Detailed Implementation
[0037] This invention proposes a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste, its preparation method, and its application. To make the advantages and technical solutions of this invention clearer and more explicit, the invention will be further described below with reference to specific embodiments.
[0038] All the raw materials mentioned in this invention can be purchased through commercial channels.
[0039] The evaluation method for the carbon-based π-complex material prepared by this invention is carried out according to the following steps:
[0040] Detection method: A fixed-bed reactor was used, and the concentration of CS2 at the outlet was detected by gas chromatograph (GC-9720P1us).
[0041] Experimental conditions: air velocity 60,000 h⁻¹ -1 The temperature was 25°C. The simulated gas composition was: 40% CH4, 20% CO, 35% H2, 500 ppm CS2, and balanced nitrogen. A saturator system was used to supply water, and the water content was expressed as relative humidity (RH).
[0042] Evaluation method: The desulfurization efficiency is obtained by the change in CS2 concentration in the flue gas before and after the process. The calculation method is shown in Equation (1).
[0043]
[0044] In equation (1): C in This indicates the concentration of CS2 before the adsorption reaction, in mg / m³. 3 C out This indicates the concentration of CS2 after the adsorption reaction, in mg / m³. 3 .
[0045] Capacity represents the mass of CS2 adsorbed per unit mass of carbon-based π-complex material, and is calculated as shown in equation (2).
[0046]
[0047] In equation (2), C in This indicates the concentration of CS2 before the adsorption reaction, in mg / m³. 3 Cout This indicates the concentration of CS2 after the adsorption reaction, in mg / m³. 3 .
[0048] The main technical concept of this invention lies in addressing the technical problem of low specific surface area, uneven pore distribution, and low pollutant removal efficiency caused by the lack of metal loading sites in existing adsorbent technologies that only use sodium alginate as a carbon source. This invention uses mannitol as an excipient and sodium hyaluronate as a water-retaining agent, mixing them with dried sodium alginate to prepare a mixed solution. The synergistic treatment using Sr and Gd as loading metals improves the high-speed, high-pressure resistance of the carbon-based π-complex adsorbent and promotes the generation of surface-active components and oxygen vacancies. Doping with phosphorus and adding polystyrene microspheres and hexadecyltrimethylammonium chloride gives the adsorbent adjustable pore size, abundant pores, high specific surface area, and numerous active sites, resulting in hydrogel spheres with more regular shapes and stronger internal structural support. Dimethylformamide and methyl acrylate jointly regulate the film-forming properties of the hydrogel, facilitating subsequent loading of metal ions and phosphorus doping. Polystyrene microspheres are cross-linked with phenylboronic acid to form borate ester bonds (BO), making the adsorbent material structure more robust. Using hexadecyltrimethylammonium chloride as a surfactant in the process of making hydrogel spheres, micelles are formed, which can reduce the surface tension of metal ion solutions and have amphiphilic characteristics, which can meet the requirements of removing CS2 from gasified fuel gas of organic solid waste in dry and humid environments.
[0049] C6H5B(OH)2+2ROH→C6H5B(OR)2+2H2O
[0050] The present invention will be further described below with reference to specific embodiments.
[0051] Example 1:
[0052] This invention discloses a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste. The preparation method includes the following steps:
[0053] Step 1: Weigh 2g of sodium hyaluronate, 2g of mannitol, and 1g of sodium alginate dried at 600℃ for 2 hours and completely dissolve them in 600mL of deionized water to prepare mixed solution one; the total mass percentage of sodium hyaluronate, mannitol, and sodium alginate in mixed solution one is 8%.
[0054] Step 2: Prepare Solution A: Mix 1 mL of dimethylformamide and 0.05 mL of methyl acrylate. Slowly add 1 mL of deionized water to the mixture to induce micelle aggregation. Add another 7 mL of deionized water to inhibit aggregation. Add distilled water to the total volume of the solution to 500 mL, heat to 60°C, and stir at this temperature for 1 hour. Prepare Solution B: Mix 1 g of polystyrene microspheres and 1 g of hexadecyltrimethylammonium chloride. Add 0.3 g of phenylboronic acid to chemically bond with the polystyrene microspheres. Mix Solution A and Solution B to form Mixed Solution II. Add Mixed Solution II to Mixed Solution I, then add 3 g of sodium tripolyphosphate as a crosslinking agent. Control the reaction temperature at 60°C and stir for 3 hours to obtain Mixed Solution III.
[0055] Step 3: Weigh 1g of Sr(NO3)2 and 1g of Gd(NO3)3·6H2O, dissolve them in distilled water to make the mass ratio of Sr:Gd 1:1, and prepare a mixed salt solution. Using a microwave impregnation method, three drops of the well-stirred mixed solution are added to the equal-mass-fraction mixed salt solution via a peristaltic pump. A microwave hydrothermal synthesizer is used, with an impregnation time of 30 minutes, a temperature of 45℃, and a microwave frequency of 200GHz, thereby preparing a hydrogel doped with metal ions.
[0056] Step 4: Wash the hydrogel repeatedly with deionized water 6 times to remove excess metal ions. Place the hydrogel doped with metal ions in a freeze dryer and freeze dry for 24 hours. Then, freeze dry it under vacuum at -60℃ and 10 Pa. Finally, place it in a tube furnace and carbonize it at 100% N2 atmosphere and 900℃ (heating rate 5℃ / min) for 2 hours to prepare a metal oxide supported carbon-based π-complex material with adjustable pore size.
[0057] The electron microscope image of the carbon-based π-complex material prepared in this embodiment is shown below. Figure 1 As shown, from Figure 1 It can be seen that carbon-based π-complex materials exhibit a layered structure. Under high temperature conditions, polystyrene microspheres are transformed into a graphitized carbon structure and form a more stable π-π complex stacked π-complex structure with the aromatic carbon skeleton of sodium alginate. At the same time, the adsorbent surface is smooth and visible nanoparticle aggregation, exhibiting a layered structure with higher porosity.
[0058] The phosphorus-doped metal oxide-supported carbon-based π-complex material with controllable pore size prepared in this embodiment was tested under high space velocity conditions: space velocity 60,000 h⁻¹. -1The temperature was 25℃. The simulated gas consisted of 40% CH4, 20% CO, 35% H2, and 5% CS2 by mass percentage, with a CS2 concentration of 200 ppm, plus a balance gas N2. A saturator system was used for water supply, with water content expressed as relative humidity (RH). A mass flow controller was used to control the total flow rate at 1 L / min. The desulfurization efficiency was measured to be 97.36%.
[0059] Example 2:
[0060] The difference from Example 1 is that in the first step, the mass ratio of sodium hyaluronate, mannitol, and sodium alginate is 1:1:1; and the total mass percentage of sodium alginate, sodium hyaluronate, and mannitol in mixed solution one is 8%.
[0061] The desulfurization efficiency was found to be 91.04% after testing.
[0062] Example 3:
[0063] The difference from Example 1 is that in the first step, the mass ratio of sodium hyaluronate, mannitol, and sodium alginate is 1:4:2; and the total mass percentage of sodium hyaluronate, mannitol, and sodium alginate in mixed solution one is 8%.
[0064] The desulfurization efficiency was tested and found to be 93.42%.
[0065] Example 4:
[0066] The difference from Example 1 is that in the first step, the mass ratio of sodium hyaluronate, mannitol and sodium alginate is 4:1:2, and the total mass percentage of sodium hyaluronate, mannitol and sodium alginate in the mixed solution is 8%.
[0067] The desulfurization efficiency was found to be 95.59% after testing.
[0068] Example 5:
[0069] The difference from Example 1 is that in the first step, the mass ratio of sodium hyaluronate, mannitol and sodium alginate is 2:1:2, and the total mass percentage of sodium hyaluronate, mannitol and sodium alginate in mixed solution one is 8%.
[0070] The desulfurization efficiency was tested and found to be 89.95%.
[0071] Example 6:
[0072] The difference from Example 1 is that in the first step, the total mass percentage of sodium hyaluronate, mannitol, and sodium alginate is 6%.
[0073] The desulfurization efficiency was tested and found to be 92.75%.
[0074] Example 7:
[0075] The difference from Example 1 is that the reaction temperature in the second step is 40°C and the carbonization temperature in the third step is 500°C.
[0076] The desulfurization efficiency was found to be 88.46% after testing.
[0077] Example 8:
[0078] The difference from Example 1 is that in the third step, the microwave immersion time is 15 minutes, the temperature is 40°C, and the microwave frequency is 50 GHz.
[0079] The desulfurization efficiency was tested and found to be 92.80%.
[0080] Example 9:
[0081] The difference from Example 1 is that after the adsorption experiment in Example 1, the adsorbent was regenerated in a tube furnace at 400°C and N2 atmosphere (flow rate of 50 mL / min) at a heating rate of 10°C / min for 2 hours to desorb and regenerate it, and then the desulfurization experiment was carried out. The above process was repeated 3 times (denoted as R1, R2 and R3 respectively).
[0082] After testing, the desulfurization efficiency of R1 was 92.57%, that of R2 was 83.79%, and that of R3 was 82.64%.
[0083] The removal efficiency and removal amount of CS2 by the carbon-based π-complex materials prepared in Examples 1-8 above are as follows: Figure 2 As shown. The removal efficiency and removal amount of CS2 by the carbon-based π-complex material regenerated multiple times in Example 9 above are as follows. Figure 3 As shown. From Figure 2 It can be seen that when the mass ratio of hyaluronic acid, mannitol, and sodium alginate is 2:2:1, the adsorbent maintains the highest removal rate of CS2 for the longest time and has the largest total adsorption volume, resulting in the best removal effect. Figure 3 It can be seen that after the first thermal regeneration treatment, its CS2 adsorption capacity decreased by only 0.14%, and the adsorption efficiency remained at a high level after three regenerations, showing good regeneration performance.
[0084] Comparative Example 1:
[0085] The difference from Example 1 is that polystyrene microspheres and hexadecyltrimethylammonium chloride are not added.
[0086] The specific preparation steps are as follows:
[0087] Step 1: Weigh 2g of sodium hyaluronate, 2g of mannitol, and 1g of sodium alginate dried at 600℃ for 2 hours, and completely dissolve them in 600mL of deionized water to prepare mixed solution one; the total mass percentage of sodium alginate, sodium hyaluronate, and mannitol in mixed solution one is 8%.
[0088] Step 2: Prepare Solution A: Mix 1 mL of dimethylformamide and 0.05 mL of methyl acrylate. Slowly add 1 mL of deionized water to the mixture to induce micelle aggregation. Add another 7 mL of deionized water to inhibit aggregation. Add distilled water to the total volume of the solution to 500 mL, heat to 60°C, and stir at this temperature for 1 hour. Prepare Solution B: Mix 1 g of polystyrene microspheres and 1 g of hexadecyltrimethylammonium chloride. Add 0.3 g of phenylboronic acid to chemically bond with the polystyrene microspheres. Mix Solution A and Solution B to form Mixed Solution II. Add Mixed Solution II to Mixed Solution I, then add 3 g of sodium tripolyphosphate as a crosslinking agent. Control the reaction temperature at 60°C and stir for 3 hours to obtain Mixed Solution III.
[0089] Step 3: Weigh 1g of Sr(NO3)2 and 1g of Gd(NO3)3·6H2O, dissolve them in distilled water to make the mass ratio of Sr:Gd 1:1, and prepare a mixed salt solution. Using a microwave impregnation method, three drops of the well-stirred mixed solution are added to the equal-mass-fraction mixed salt solution via a peristaltic pump. A microwave hydrothermal synthesizer is used, with an impregnation time of 30 minutes, a temperature of 45℃, and a microwave frequency of 200GHz, thereby preparing a hydrogel doped with metal ions.
[0090] Step 4: Wash the hydrogel repeatedly with deionized water 6 times to remove excess metal ions. Place the hydrogel doped with metal ions in a freeze dryer and freeze dry for 24 hours. Then, freeze dry it under vacuum at -60℃ and 10 Pa. Finally, place it in a tube furnace and carbonize it at 100% N2 atmosphere and 900℃ (heating rate 5℃ / min) for 2 hours to prepare an adsorbent material.
[0091] The adsorbent material prepared in this comparative example was tested under high space velocity conditions, with specific steps following those in Example 1. The results showed that the pollutant removal efficiency decreased, with a desulfurization efficiency of 87.14%.
[0092] Comparative Example 2:
[0093] The difference from Example 1 is that sodium hyaluronate and mannitol are not added.
[0094] Step 1: Weigh 1g of sodium alginate dried at 600℃ for 2 hours and completely dissolve it in 600mL of deionized water to prepare sodium alginate solution 1; the mass percentage of sodium alginate in mixed solution 1 is 8%.
[0095] Step 2: Prepare Solution A: Mix 1 mL of dimethylformamide and 0.05 mL of methyl acrylate. Slowly add 1 mL of deionized water to the mixture to induce micelle aggregation. Add another 7 mL of deionized water to inhibit aggregation. Add distilled water to the total volume of the solution to 500 mL, heat to 60°C, and stir at this temperature for 1 hour. Prepare Solution B: Mix 1 g of polystyrene microspheres and 1 g of hexadecyltrimethylammonium chloride. Add 0.3 g of phenylboronic acid to chemically bond with the polystyrene microspheres. Mix Solution A and Solution B to form Mixed Solution II. Add Mixed Solution II to Mixed Solution I, then add 3 g of sodium tripolyphosphate as a crosslinking agent. Control the reaction temperature at 60°C and stir for 3 hours to obtain Mixed Solution III.
[0096] Step 3: Weigh 1g of Sr(NO3)2 and 1g of Gd(NO3)3·6H2O, dissolve them in distilled water to make the mass ratio of Sr:Gd 1:1, and prepare a mixed salt solution. Using a microwave impregnation method, three drops of the well-stirred mixed solution are added to the equal-mass-fraction mixed salt solution via a peristaltic pump. A microwave hydrothermal synthesizer is used, with an impregnation time of 30 minutes, a temperature of 45℃, and a microwave frequency of 200GHz, thereby preparing a hydrogel doped with metal ions.
[0097] Step 4: Wash the hydrogel repeatedly with deionized water 6 times to remove excess metal ions. Place the hydrogel doped with metal ions in a freeze dryer and freeze dry for 24 hours. Then, freeze dry it under vacuum at -60℃ and 10 Pa. Finally, place it in a tube furnace and carbonize it at 100% N2 atmosphere and 900℃ (heating rate 5℃ / min) for 2 hours to prepare an adsorbent material.
[0098] The adsorbent material prepared in this comparative example was tested under high space velocity conditions, with specific steps referring to Example 1. The results showed that the pollutant removal efficiency decreased, and the desulfurization efficiency was 88.03%.
[0099] Comparative Example 3:
[0100] The difference from Example 1 is that there is no second step in the preparation process.
[0101] Step 1: Weigh 2g of sodium hyaluronate, 2g of mannitol, and 1g of sodium alginate dried at 600℃ for 2 hours and completely dissolve them in 600mL of deionized water to prepare mixed solution one; the total mass percentage of sodium hyaluronate, mannitol, and sodium alginate in mixed solution one is 8%.
[0102] The second step involves weighing 1g of Sr(NO3)2 and 1g of Gd(NO3)3·6H2O, dissolving them in distilled water to achieve a Sr:Gd mass ratio of 1:1, and preparing a mixed salt solution. Using a microwave impregnation method, the well-stirred mixed solution is added dropwise to the equal-mass-fraction mixed salt solution via a peristaltic pump. A microwave hydrothermal synthesizer is used, with an impregnation time of 30 minutes, a temperature of 45℃, and a microwave frequency of 200GHz, thereby preparing a hydrogel doped with metal ions.
[0103] The third step involves repeatedly washing the hydrogel with deionized water six times to remove excess metal ions. The hydrogel doped with metal ions is then freeze-dried in a freeze dryer for 24 hours, followed by vacuum freeze-drying at -60℃ and 10Pa. Finally, it is carbonized in a tube furnace at 100% N2 atmosphere and 900℃ (heating rate 5℃ / min) for 2 hours to prepare an adsorbent material.
[0104] The adsorbent material prepared in this comparative example was tested under high air velocity conditions, with specific steps following those described in Example 1. The results showed that the pollutant removal efficiency decreased, with a desulfurization efficiency of 79.10%.
[0105] Comparative Example 4:
[0106] The difference from Example 1 is that phenylenediamine is used as the crosslinking agent in this comparative example.
[0107] The specific steps are as follows:
[0108] Step 1: Weigh 2g of sodium hyaluronate, 2g of mannitol, and 1g of sodium alginate dried at 600℃ for 2 hours and completely dissolve them in 600mL of deionized water to prepare mixed solution one; the total mass percentage of sodium hyaluronate, mannitol, and sodium alginate in mixed solution one is 8%.
[0109] Step 2: Prepare Solution A: Mix 1 mL of dimethylformamide and 0.05 mL of methyl acrylate. Slowly add 1 mL of deionized water to the mixture to induce micelle aggregation. Add another 7 mL of deionized water to inhibit aggregation. Add distilled water to the total volume of the solution to 500 mL, heat to 60°C, and stir at this temperature for 1 hour. Prepare Solution B: Mix 1 g of polystyrene microspheres and 1 g of hexadecyltrimethylammonium chloride. Add 0.3 g of phenylboronic acid to chemically bond with the polystyrene microspheres. Mix Solution A and Solution B to form Mixed Solution II. Add Mixed Solution II to Mixed Solution I, then add 3 g of phenylenediamine as a crosslinking agent. Control the reaction temperature at 60°C and stir for 3 hours to obtain Mixed Solution III.
[0110] Step 3: Weigh 1g of Sr(NO3)2 and 1g of Gd(NO3)3·6H2O, dissolve them in distilled water to make the mass ratio of Sr:Gd 1:1, and prepare a mixed salt solution. Using a microwave impregnation method, three drops of the well-stirred mixed solution are added to the equal-mass-fraction mixed salt solution via a peristaltic pump. A microwave hydrothermal synthesizer is used, with an impregnation time of 30 minutes, a temperature of 45℃, and a microwave frequency of 200GHz, thereby preparing a hydrogel doped with metal ions.
[0111] Step 4: Wash the hydrogel repeatedly with deionized water 6 times to remove excess metal ions. Place the hydrogel doped with metal ions in a freeze dryer and freeze dry for 24 hours. Then, freeze dry it under vacuum at -60℃ and 10 Pa. Finally, place it in a tube furnace and carbonize it at 100% N2 atmosphere and 900℃ (heating rate 5℃ / min) for 2 hours to prepare an adsorbent material.
[0112] The adsorbent material prepared in this comparative example was tested under high space velocity conditions, with specific steps following those in Example 1. The results showed that the pollutant removal efficiency decreased, with a desulfurization efficiency of 93.95%.
[0113] Comparative Example 5:
[0114] The difference from Example 1 is that the metal salt solution used in this comparative example is AlCl3·6H2O.
[0115] Step 1: Weigh 2g of sodium hyaluronate, 2g of mannitol, and 1g of sodium alginate dried at 600℃ for 2 hours and completely dissolve them in 600mL of deionized water to prepare mixed solution one; the total mass percentage of sodium hyaluronate, mannitol, and sodium alginate in mixed solution one is 8%.
[0116] Step 2: Prepare Solution A: Mix 1 mL of dimethylformamide and 0.05 mL of methyl acrylate. Slowly add 1 mL of deionized water to the mixture to induce micelle aggregation. Add another 7 mL of deionized water to inhibit aggregation. Add distilled water to the total volume of the solution to 500 mL, heat to 60°C, and stir at this temperature for 1 hour. Prepare Solution B: Mix 1 g of polystyrene microspheres and 1 g of hexadecyltrimethylammonium chloride. Add 0.3 g of phenylboronic acid to chemically bond with the polystyrene microspheres. Mix Solution A and Solution B to form Mixed Solution II. Add Mixed Solution II to Mixed Solution I, then add 3 g of sodium tripolyphosphate as a crosslinking agent. Control the reaction temperature at 60°C and stir for 3 hours to obtain Mixed Solution III.
[0117] Step 3: Weigh 1g of AlCl3·6H2O and dissolve it in distilled water to prepare a salt solution. Using the microwave impregnation method, three drops of the well-stirred mixed solution are added to the salt solution of equal mass fraction using a peristaltic pump. A microwave hydrothermal synthesizer is used, with a microwave impregnation time of 30 minutes, a temperature of 45℃, and a microwave frequency of 200GHz, thereby preparing a hydrogel doped with metal ions.
[0118] Step 4: Wash the hydrogel repeatedly with deionized water 6 times to remove excess metal ions. Place the hydrogel doped with metal ions in a freeze dryer and freeze dry for 24 hours. Then, freeze dry it under vacuum at -60℃ and 10 Pa. Finally, place it in a tube furnace and carbonize it at 100% N2 atmosphere and 900℃ (heating rate 5℃ / min) for 2 hours to prepare an adsorbent material.
[0119] The adsorbent material prepared in this comparative example was tested under high air velocity conditions, with specific steps following those in Example 1. The results showed that the pollutant removal efficiency decreased, with a desulfurization efficiency of 90.13%.
[0120] Comparative Example 6:
[0121] The difference from Example 1 is that sodium alginate that is not dried at high temperature is used as the carbon source.
[0122] Step 1: Weigh 2g of sodium hyaluronate, 2g of mannitol, and 1g of sodium alginate and dissolve them completely in 600mL of deionized water to prepare mixed solution one; the total mass percentage of sodium hyaluronate, mannitol, and sodium alginate in mixed solution one is 8%.
[0123] Step 2: Prepare Solution A: Mix 1 mL of dimethylformamide and 0.05 mL of methyl acrylate. Slowly add 1 mL of deionized water to the mixture to induce micelle aggregation. Add another 7 mL of deionized water to inhibit aggregation. Add distilled water to the total volume of the solution to 500 mL, heat to 60°C, and stir at this temperature for 1 hour. Prepare Solution B: Mix 1 g of polystyrene microspheres and 1 g of hexadecyltrimethylammonium chloride. Add 0.3 g of phenylboronic acid to chemically bond with the polystyrene microspheres. Mix Solution A and Solution B to form Mixed Solution II. Add Mixed Solution II to Mixed Solution I, then add 3 g of sodium tripolyphosphate as a crosslinking agent. Control the reaction temperature at 60°C and stir for 3 hours to obtain Mixed Solution III.
[0124] Step 3: Weigh 1g of Sr(NO3)2 and 1g of Gd(NO3)3·6H2O, dissolve them in distilled water to make the mass ratio of Sr:Gd 1:1, and prepare a mixed salt solution. Using a microwave impregnation method, three drops of the well-stirred mixed solution are added to the equal-mass-fraction mixed salt solution via a peristaltic pump. A microwave hydrothermal synthesizer is used, with an impregnation time of 30 minutes, a temperature of 45℃, and a microwave frequency of 200GHz, thereby preparing a hydrogel doped with metal ions.
[0125] Step 4: Wash the hydrogel repeatedly with deionized water 6 times to remove excess metal ions. Place the hydrogel doped with metal ions in a freeze dryer and freeze dry for 24 hours. Then, freeze dry it under vacuum at -60℃ and 10 Pa. Finally, place it in a tube furnace and carbonize it at 100% N2 atmosphere and 900℃ (heating rate 5℃ / min) for 2 hours to prepare a metal oxide supported adsorbent material with adjustable pore size.
[0126] The adsorbent material prepared in this comparative example was tested under high air velocity conditions, with specific steps following those in Example 1. The results showed that the pollutant removal efficiency decreased, with a desulfurization efficiency of 86.62%.
[0127] The removal efficiency and removal amount of CS2 by the adsorbent materials prepared in Comparative Examples 1-6 are shown in Table 1. Table 1 shows that the adsorption efficiency and adsorption capacity of the adsorbents prepared in the comparative examples are not high. Compared with the adsorption efficiency of Example 1, the experimental conditions of Example 1 are optimal, resulting in the best CS2 removal efficiency.
[0128] Table 1
[0129] Comparative Example 1 87.14 273.19 Comparative Example 2 88.03 279.82 Comparative Example 3 79.10 234.78 Comparative Example 4 93.95 317.36 Comparative Example 5 90.13 302.89 Comparative Example 6 86.62 269.57
[0130] Those skilled in the art should recognize that the above embodiments are only used to illustrate this application and are not intended to limit this application. Any appropriate changes and variations made to the above embodiments within the essential spirit and scope of this application fall within the scope of protection claimed in this application.
Claims
1. A method for preparing a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste, characterized in that, Includes the following steps: a. Mix sodium hyaluronate, mannitol and dried sodium alginate in a certain ratio to prepare mixed solution one; b. Prepare solution A: Mix dimethylformamide and methyl acrylate; Solution B is prepared by mixing polystyrene microspheres with a surfactant and then adding phenylboronic acid, which causes the polystyrene microspheres to form chemical bonds with the phenylboronic acid. Solution A and solution B are mixed to form mixed solution two; Add the second mixed solution to the first mixed solution, then add sodium tripolyphosphate as a crosslinking agent, and stir while controlling the reaction temperature at 40-60 ℃ to obtain the third mixed solution; c. Using the microwave impregnation method, add three drops of the mixed solution to a solution containing Sr. 2+ Gd 3+ In a salt solution, a hydrogel doped with metal ions was obtained; d. The hydrogel doped with metal ions is dried, frozen, and then carbonized by high-temperature calcination under a nitrogen atmosphere to obtain carbon-based π-complex materials. In step a, the mass ratio of sodium hyaluronate, mannitol, and sodium alginate is 1-2:1-4:1-4, the solvent of mixed solution one is water, and the total mass percentage of sodium hyaluronate, mannitol, and sodium alginate in mixed solution one is 6-8%. In step b, the total amount of dimethylformamide and methyl acrylate added is 15-35% of the total mass of sodium hyaluronate, mannitol, and sodium alginate; the amount of polystyrene microspheres and surfactant added is 3-5% of the total mass of sodium hyaluronate, mannitol, and sodium alginate; the surfactant is hexadecyltrimethylammonium chloride; the amount of crosslinking agent added is 60% of the total mass of sodium hyaluronate, mannitol, and sodium alginate; and the amount of phenylboronic acid added is 0.3 times the amount of polystyrene microspheres added. In step c, Sr 2+ Gd 3+ The mass ratio of the two metals in the salt solution is 1:1, Sr 2+ Gd 3+ The salt solution is Sr(NO3)2 and Gd(NO3)3•6H2O.
2. The method for preparing a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste according to claim 1, characterized in that: In step c, the microwave immersion time is 20–40 min, the immersion temperature is 40–50 °C, and the microwave frequency is 200 GHz.
3. The method for preparing a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste according to claim 1, characterized in that: In step d, the carbonization temperature is 300–900 °C and the carbonization time is 1–3 h. After carbonization, the metal ions in the hydrogel doped with metal ions are oxidized to their corresponding oxides to adsorb CS2 in the gasification fuel of organic solid waste.
4. The method for preparing a carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste according to claim 1, characterized in that: In step a, sodium alginate is used as a carrier, mannitol is used as an excipient for the sodium alginate carrier, and sodium hyaluronate is used as a water-retaining agent to facilitate the removal of CS2.
5. A carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 4, and the carbon-based π-complex material has a layered structure.
6. The application of the carbon-based π-complex material for removing CS2 from gasified fuel gas of organic solid waste according to claim 5, characterized in that: The carbon-based π-complex material was tested in a fixed-bed reactor with a simulated gas flow rate of 60,000 h⁻¹. -1 CS2 is removed from the gasification fuel of organic solid waste at a temperature of 25 ℃; the simulated gas consists of 40% CH4, 20% CO, 35% H2 and 5% CS2 by mass percentage, wherein the concentration of CS2 is 200 ppm.
Citation Information
Patent Citations
Preparation method and application of copper alginate aerosol catalyst with high catalytic activity
CN113941363A
Three-dimensional silver-based composite aerogel, preparation method and application thereof
CN116813976B
Floating copper-loaded sodium alginate hydrogel sphere and preparation method and application thereof
CN119385149B
Composite adsorption material for removing heavy metal ions and preparation method and application of composite adsorption material
CN103752286A
Supported catalyst for removing COS in blast furnace gas at low temperature and preparation method
CN118616108A